2015
DOI: 10.14260/jemds/2015/550
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutritional Status by Mid Upper Arm Circumference (Muac) Among Rural Children of Katihar District in Kosi Region of Bihar

Abstract: An observational study of 500 children (267 boys and 233 girls) was undertaken during 2008-2010 at primary health centres under the aegis of Katihar Medical College in Kosi region of Bihar to assess their nutritional status using mid upper arm circumference (MUAC) in Katihar district of Bihar. Children from remote villages in rural areas located approximately 30 km from Katihar district headquarters were observed. Information on age of the children were collected from their parents. Measurement was recorded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…29 While, another study reported prevalence of undernutrition was identical in both genders. 31 Our study found similar result in both genders. Indicating that there is no gender based food disparity and resource allocation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…29 While, another study reported prevalence of undernutrition was identical in both genders. 31 Our study found similar result in both genders. Indicating that there is no gender based food disparity and resource allocation.…”
Section: Discussionsupporting
confidence: 81%
“…1,[26][27][28] On the other hand, present rate was higher than those reported from other parts of India. [29][30][31][32] Prevalence of wasting of those studies varies from 11% to 70%, Indicating nutritional status of Indian children is not satisfactory. 1,32 A study from West Bengal, India showed the percentages of under-nutrition among girls and boys were 18.46% and 19.38%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with weight for height, MUAC has a sensitivity of 24.6% and a specificity of 94.8% appears to be a better predictor of childhood mortality than is weight for height. 7 Nutritional status plays a vital role in determining the health status particularly in children. Accurate assessment of nutritional status is a requisite in proper planning, effective implementation and evaluation of nutrition interventions.…”
mentioning
confidence: 99%
“…[4][5][6] Whereas any damage due to nutritional deficiencies during childhood may lead to impaired cognitive development and poor educational achievement of the children. 1,[7][8][9][10][11][12][13] Earlier studies findings report that adequate diet consistently tends to have an excellent nutritional profile and good educational achievement among children. [14][15][16][17][18] Therefore, it is essential to ensure that an adequate and sufficient nutritious diet for every child is important to shape a healthy and productive future.…”
Section: Introductionmentioning
confidence: 99%